Sourcing Rhizobium leguminosarum biovar viciae strains from Mediterranean centres of origin to optimize nitrogen fixation in forage legumes grown on acid soils. (25th March 2021) - Yates, Ron J.; Harrison, Robert J.; Loi, Angelo; Steel, Emma J.; Edwards, Tom J.; Nutt, Brad J.; Porqueddu, Claudio; Gresta, Fabio; Howieson, John G.
Abstract: Over the last three decades, farming systems in Europe and Australia have seen a decline in legume plantings, leading to reduced soil carbon and fertility, and an increase in plant disease, reliance on industrial nitrogen fertilizer and herbicides. In Australia, one reason for this decline has been the movement towards sowing crops and forages into dry soil, before the opening rains, as a consequence of climate variability. This practice predicates against the survival of rhizobial inoculants, and hence generates uncertainty about legume performance. The research reported here was initiated to improve the robustness of a specific forage legume/rhizobia symbiosis to increase nitrogen fixation in low pH, infertile soils. Rhizobial strains ( Rhizobium leguminosarum biovar viciae ) from Pisum sativum L. were sourced from acid soils in southern Italy and southern Australia. Strains were evaluated for N fixation on the forage legumes P . sativum, Vicia sativa and Vicia villosa, then for survival and persistence in acid soils (pHCa 4.6). Fourteen of the strains produced a higher percentage of nitrogen derived from the atmosphere (%Ndfa) compared to commercial comparator strain SU303 (<78%). Twenty‐two strains survived sufficiently into the second season to form more nodules than SU303, which only achieved 3% of plants nodulated. Elite strains WSM4643 and WSM4645 produced six times more nodulated plants than SU303 and had significantly higher saprophytic competence in acid soil. These strains have the ability to optimize symbiotic associations with field peas and vetch in soils with low fertility, carbon and pH that are restrictive to the current commercial strain SU303.